(untitled) (Comprehensive Journal of Science, 2025)
Background: Chronic inflammation associated with diabetes often lead to abnormal lipid levels and oxidative stress, both of which play a key role in the progression of metabolic syndrome. Researchers continue to investigate medications aimed at preventing or managing diabetes-related complications. This study investigated the therapeutic potential of three herbal extracts by assessing their impact on macrophage oxidative bioactive marker expression in metabolic disorders and comparing the results with those of conventional Western medicine. Method: In this study, the following inhibited concentrations were applied to treat LPS-stimulated inflammation in high-glucose mimic cell cultures: Artemisia afra (200 µg/ml), Cinnamon verum (250 µg/ml), Fenugreek (2500 µg/ml), and metformin (200 µg/ml). Results: LPL is significantly overexpressed, while SOD-2 activity is suppressed in the presence of high glucose, both with and without stimulation by LPSactivated macrophage cells. A. afra and C. verum extracts promoted cell growth under high glucose conditions more effectively than Fenugreek and metformin. Cinnamon verum significantly enhances the antioxidant enzyme SOD-2 and effectively downregulates the LPL enzyme under high glucose conditions, both in the presence and absence of stimulation. Compared to Artemisia afra, fenugreek, or metformin. In conclusion: These herbs help regulate metabolic markers in diabetic patients may help prevent diabetes progression, treat atherosclerosis, and manage chronic inflammation while supporting glucose control. Future investigations are essential to identify and understand the bioactive molecules in these herbal therapies involved in this protocol.